2014
DOI: 10.1177/0272431614529366
|View full text |Cite
|
Sign up to set email alerts
|

Worry in Children

Abstract: Worry in adults has been conceptualized as a thinking process involving problem-solving attempts about anticipated negative outcomes. This process is related to, though distinct from, fear. Previous research suggested that compared to adults, children's experience of worry is less strongly associated with thinking and more closely related to fear. The present study further explored children's worrying. Ninety-three 7-to 12-yearolds rated how much they worry, fear and think about the same list of negative outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
(71 reference statements)
1
5
0
Order By: Relevance
“…In line with these findings, Carr and Szabó (2015) showed that children (7-12 years) associated their experience of worry as more closely related to fear of negative outcomes as opposed to thinking about negative outcomes. However, this relationship was moderated by age, as older children tended to report their worries as more strongly associated with thinking and less closely related to fear.…”
Section: Verbal Worrysupporting
confidence: 70%
See 1 more Smart Citation
“…In line with these findings, Carr and Szabó (2015) showed that children (7-12 years) associated their experience of worry as more closely related to fear of negative outcomes as opposed to thinking about negative outcomes. However, this relationship was moderated by age, as older children tended to report their worries as more strongly associated with thinking and less closely related to fear.…”
Section: Verbal Worrysupporting
confidence: 70%
“…Seven studies examined the verbal nature of worry in youth (see Table 3). Two studies used a modified version of The Child and Adolescent Worry questionnaire (CAW) to investigate whether children conceptualise worry as a process related to their fear of negative outcomes or the extent to which they think about negative outcomes (Szabó 2007;Carr and Szabó 2015). Szabó (2007) found that children (mean age of 9 years) reported their worries to be related to both fear and thinking processes, although the extent to which they reported fear of negative outcomes was relatively stronger than the extent to which they think about them, and this was more prominent for physical worries rather than for social worries.…”
Section: Verbal Worrymentioning
confidence: 99%
“…There was a significant difference between the groups on PB scores only, with the older group scoring higher. Carr and Szabó (2015) in a non-clinical sample, age range 7–12, examined only PB and found no relationship between this subscale and age.…”
Section: Resultsmentioning
confidence: 98%
“…Eleven articles (Bacow et al, 2009; Irak, 2012; Smith and Hudson, 2013; Benedetto et al, 2014; Holmes et al, 2014; Carr and Szabó, 2015; Donovan et al, 2017; Francis et al, 2017, 2018; Hearn et al, 2017a), representing 10 separate samples reported Cronbach alphas for the MCQ-C (two studies Francis et al, 2017 and Francis et al, 2018 reported Cronbach alphas for different parts of the scale in the same sample). Internal reliability of the MCQ-C total score was adequate to good in the three studies that reported it (range 0.73 to 0.87).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation